Physical activity for the prevention and treatment of major chronic disease: an overview of systematic reviews. - Nunan, D; Mahtani, K; Roberts, N; Heneghan, C (2013)
BACKGROUND: The evidence that higher levels of physical activity and/or lower levels of physical inactivity are associated with beneficial health-related outcomes stems mainly from observational studies. Findings from these studies often differ from randomised controlled trials and systematic reviews currently demonstrate mixed results, due partly to heterogeneity in physical activity interventions, methodologies used and populations studied. As a result, translation into clinical practice has been difficult. It is therefore essential that an overview is carried out to compare and contrast systematic reviews, and to identify those physical activity interventions that are the most effective in preventing and/or treating major chronic disease. This protocol has been registered on PROSPERO 2013: CRD42013003523. METHODS: We will carry out an overview of Cochrane systematic reviews. We will search the Cochrane Database of Systematic Reviews for systematic reviews of randomised controlled trials that have a primary focus on disease-related outcomes. We will restrict reviews to those in selected major chronic diseases. Two authors will independently screen search outputs, select studies, extract data and assess the quality of included reviews using the assessment of multiple systematic reviews tool; all discrepancies will be resolved by discussing and reaching a consensus, or by arbitration with a third author. The data extraction form will summarise key information from each review, including details of the population(s) (for example, disease condition), the context (for example, prevention, treatment or management), the participants, the intervention(s), the comparison(s) and the outcomes. The primary outcomes of interest are the prevention of chronic disease and/or improved outcomes, in the treatment or management of chronic disease. These outcomes will be summarised and presented for individual chronic diseases (for example, any change in blood pressure in hypertension or glucose control in diabetes). Secondary outcomes of interest are to describe the structure and delivery of physical activity interventions across chronic disease conditions and adverse events associated with physical activity. DISCUSSION: We anticipate that our results could inform researchers, guideline groups and policymakers of the most efficacious physical activity interventions in preventing and/or managing major chronic disease.